2020
DOI: 10.18510/hssr.2020.8118
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Weaknesses of Internal Control of Local Governments in Indonesia

Abstract: Purpose of the study: This paper aims to examine the factors influencing local government internal control weakness, includes leverage, locally generated revenue, capital expenditure, complexity, previous year's internal control weaknesses findings Methodology: The population of this research is the audit report of the Audit Board of the Republic of Indonesia (BPK) in the Regency/City of West Indonesia with a total of 263 financial statements. The purposive sampling method is used, resulting in 186 finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These results suggest that larger LGAs increase the likelihood of financial statement error/restatement and, therefore, are more likely to produce lower financial statement quality. Consistent with previous research conducted by (Kiswanto et al, 2020) in the context of LGAs, they found that larger LGAs produce lower quality financial statements.…”
Section: Size Of Lgas and Quality Of Financial Statementssupporting
confidence: 89%
See 2 more Smart Citations
“…These results suggest that larger LGAs increase the likelihood of financial statement error/restatement and, therefore, are more likely to produce lower financial statement quality. Consistent with previous research conducted by (Kiswanto et al, 2020) in the context of LGAs, they found that larger LGAs produce lower quality financial statements.…”
Section: Size Of Lgas and Quality Of Financial Statementssupporting
confidence: 89%
“…However, various measures of size have been employed in a public setting. For instance, Kiswanto et al (2020) argued that capital expenditure is similar to the amount used to acquire fixed assets and, therefore, a more appropriate measure of size (Kiswanto et al, 2020). While Sebayang (2018) argues that the size of LGAs can be assessed by their physical appearance.…”
Section: Size and Quality Of Financial Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial oversight is required. Financial supervision is also aimed at gaining sufficient confidence in the organization's efficacy and efficiency, the accuracy of financial reporting, and compliance with rules (Kiswanto et al, 2020). Regional government supervision, according to Article 16 of the President of the Republic of Indonesia's Decree No.…”
Section: B Reliability Of Financial Statementsmentioning
confidence: 99%
“…IC is a vital part of any organization, which includes local government. A system of IC is the collection of rules, processes, and policies that it has put in place to secure its assets, guarantee that its financial reports are accurate, and ensure that the business complies with all applicable laws and regulations (Hajawiyah and Mahera 2020). In local government, IC is essential for promoting transparency, accountability, and good governance.…”
Section: Introductionmentioning
confidence: 99%